A history of International Headache Society grants and their impact on headache careers. (October 2022) - Puledda, Francesca; Wang, Shuu-Jiun; Diener, Hans-Christoph; Schytz, Henrik Winther
Background: The International Headache Society has been offering multiple award opportunities for young researchers and clinicians for many years, with the aim of supporting the development of careers in headache science and medicine. Methods: In order to assess the outcomes of the International Headache Society award grants, a questionnaire was sent to all previous recipients, investigating a series of aspects related to their work, both during and after award completion. Results: Of 44 total questionnaires sent, 36 were returned. Eighty-one percent of the recipients reported to have remained in the headache field since the award, half of them held a current academic position and over three-quarters had stayed in contact with the host institution. The totality of questionnaire responders stated that the grant had had a significantly positive impact on their careers. Conclusions: The International Headache Society grants have assisted many young researchers in building an academic and clinical career in the field of headache, throughout the years.